2023
DOI: 10.1017/s0007114522003257
|View full text |Cite
|
Sign up to set email alerts
|

Association of meal timing of energy, macronutrients and foods with hypercholesterolaemia in the US adults

Abstract: Few studies examined the association of energy, macronutrients, and food consumption at dinner vs. breakfast with hypercholesterolemia. A total of 27,911 participants from the NHANES (2003-2016) were included in the cross-section study. Energy, macronutrients, and food consumption at breakfast, dinner, and the difference at dinner versus breakfast (Δratio) were calculated. Multiple logistic regression models and substitution effects of foods at dinner with breakfast were also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, higherquality reviews are needed to confirm the causation between breakfast skipping and increased LDL, as the current reviews acknowledged the possible confounding effect of food choice and quality, which had not been investigated. A recent study using national-scale representative data in the US simultaneously examined the association between meal timing and food quality (Li et al, 2023). The study reported that those who had a higher ratio of energy consumption at dinner compared to breakfast were associated with an increased risk of hypercholesterolaemia and suggested that added sugar, nuts, and processed meat to be consumed at breakfast rather than dinner to reduce the risk of prevalent hypercholesterolaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, higherquality reviews are needed to confirm the causation between breakfast skipping and increased LDL, as the current reviews acknowledged the possible confounding effect of food choice and quality, which had not been investigated. A recent study using national-scale representative data in the US simultaneously examined the association between meal timing and food quality (Li et al, 2023). The study reported that those who had a higher ratio of energy consumption at dinner compared to breakfast were associated with an increased risk of hypercholesterolaemia and suggested that added sugar, nuts, and processed meat to be consumed at breakfast rather than dinner to reduce the risk of prevalent hypercholesterolaemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, higher-quality reviews are needed to confirm the causation between breakfast skipping and increased LDL, as the current reviews acknowledged the possible confounding effect of food choice and quality, which had not been investigated. A recent study using national-scale representative data in the US simultaneously examined the association between meal timing and food quality (Li et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%